A Bibliometric Analysis of The Nexus betwen Tax Avoidance and Corporate Social Responsibility: Mapping the Intellectual Structure and Future Research Agenda - Riyani, Rita Nurul; Devano, Sony; Priyono, Agus Puji (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study seeks to have to map the development of research on the relationship between tax avoidance and Corporate Social Responsibility (CSR) through a bibliometric analysis of 760 Scopus-indexed articles published from 2015 to 2025. The analysis was conducted to have using publication trends, keyword co-occurrence, thematic networks, and topic evolution. The findings indicate to have a substantial increase in the literature, with an annual growth rate of 22.89%, positioning the nexus between tax avoidance and Corporate Social Responsibility (CSR) as the central focus of scholarly attention, supported by related themes such as corporate governance, sustainability, and ESG. This study also reveals to have a shift in the research direction toward a broader and more integrated approach. These results highlight to have the importance of transparency and sustainable tax governance for both companies and regulators. Overall, this research offers to have a comprehensive overview of the evolving dynamics of tax-related studies within the context of Corporate Social Responsibility (CSR) and can serve to have as a foundation for guiding future research directions.